Lower extremity mechanical work explains interindividual variability of running economy - Heise, G. D.; Smith, J.; Martin, P. E. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
The metabolic cost of running has been linked to the cost of supporting one`s mass and the time course of generating force during stance (Kram, 2000). Data from various animal species and speeds of locomotion support this claim (Kram & Taylor, 1990). Several researchers suggest that the mechanical work done by muscles is strongly tied to the metabolic cost of walking (e.g., Umberger & Martin, 2007). The work of DeVita et al. (2006) suggested that level walking and running result in a bias or"overproduction" of positive mechanical work by the musculature of the lower extremity in order to overcome dissipation by other tissues. For runners, they reported 8% more total positive work than negative work. Taken collectively, the aforementioned research points to the importance of the stance phase of locomotion and the mechanical power generated and dissipated in the lower extremity as potential determinants of metabolic energy cost. In the present study, correlations between running economy (RE; the metabolic cost at a given speed) and the positive and negative mechanical work at lower extremity joints were examined. It was hypothesized that the dominance of positive work during stance, especially at the hip and ankle, would be positively correlated to RE. Correlations between RE and mechanical energy dissipation (i.e., negative work) at each lower extremity joint were also investigated, but no specific hypotheses were formulated.